SITUS KAWASAN KAUMAN MENARA KUDUS SEBAGAI SUMBER BELAJAR SEJARAH - Moh Rosyid (Universitas Negeri Malang, 2021)
This reasearch aims to illuminate the fact that cultural heritage objects could be used as a source of history instructions. This research data were obtained by the authors with interviews, observations, and literature studies. Then, the data were analyzed with qualitative descriptive approaches. The results of this research show that Kudus in the pre-Islamic past left traces of a great civilization in the form of The Holy Tower, The Twin Arch (both in the Holy al-Aqsha Mosque) and The Breaking of Bubrah in the Kauman Area of the Holy Tower. This fact can be used as an reinforcement that past life that bequeaths cultural traces can be enjoyed by current and future generations as a source of historical learning in educational institutions must learn to college, especially historicalreviewers, archaeologists, sociologists, anthropologists and other scientists about Kudus. The task with Municipiality Kudus, DPRD Kudus, and Kudus citizens is to take care according to their respective portions.